Predictive value of remnant-like particle cholesterol in the prediction of long-term AF recurrence after radiofrequency catheter ablation - Wu, Bing; Liang, Zichang; Qiu, Lili; Wang, Jianan; Huang, Qianwen; Zhuang, Tingpei; Hong, Sihan; Bai, Meng (Frontiers in Cardiovascular Medicine, 2023)
Objective The relationship between remnant-like particle cholesterol (RLP-C) levels and the progression of atrial fibrillation (AF) is not known. This research aimed to explore the association of RLP-C with long-term AF recurrence events post-radiofrequency catheter ablation (RFCA) of AF. Methods In total 320 patients with AF who were subjected to the first RFCA were included in this research. Baseline information and laboratory data of patients were retrospectively collected, and a 1-year follow-up was completed. The follow-up endpoint was defined as an AF recurrence event occurring after 3 months. Afterward, a multivariate Cox regression model was constructed to analyze the risk factors that affect AF recurrence. Results AF recurrence occurred in 103 patients (32.2%) within 3–12 months after RFCA. Based on the multivariate Cox regression analysis, Early recurrence (ER) [hazard ratio (HR) =1.57, 95% confidence interval (CI): 1.04–2.36, P = 0.032)], coronary artery disease (CAD) (HR = 2.03, 95% CI: 1.22–3.38, P = 0.006), left atrium anterior-posterior diameter (LAD) (HR = 1.07, 95% CI: 1.03–1.10, P < 0.001), triglyceride (TG) (HR = 1.51, 95% CI: 1.16–1.96, P = 0.002), low-density lipoprotein cholesterol (LDL-C) (HR = 0.74, 95% CI: 0.55–0.98, P = 0.036), and RLP-C (HR = 0.75 per 0.1 mmol/L increase, 95% CI: 0.68–0.83, P < 0.001) were linked to the risk of AF recurrence. Among them, the relationship between RLP-C and AF recurrence was found for the first time. The predictive value of RLP-C for AF recurrence was analyzed utilizing receiver operating characteristic (ROC) curves [area under the curve (AUC) = 0.81, 95% CI: 0.77–0.86, P < 0.001]. Subsequently, the optimal threshold value of RLP-C was determined to be 0.645 mmol/L with a sensitivity of 87.4% and a specificity of 63.6% based on the Youden index. Additionally, Kaplan–Meier analysis indicated a lower AF recurrence rate in the >0.645 mmol/L group than in the ≤0.645 mmol/L group (Log-rank P < 0.001). Conclusion Low levels of RLP-C are associated with a higher risk of AF recurrence post-RFCA, suggesting that RLP-C may be a biomarker that helps to identify long-term AF recurrence.